Identification of mitochondrial protein complexes in Arabidopsis using two-dimensional blue-native polyacrylamide gel electrophoresis - Giege, P; Sweetlove, L; Leaver, C (2003)
Mitochondria fulfill a wide range of functions in the plant cell, including producing ATP, providing carbon skeletons for biosynthesis, and biosynthesizing vitamins and cofactors. Recently, mitochondria have been implicated in the pathway of programmed cell death in plant cells. In addition, mutations in the mitochondrial genome have been shown to be causally related to cytoplasmic male sterility - the failure to produce functional pollen in a range of crop plants. Proteomics has been used to attempt to catalogue mitochondrial proteins and extend our understanding of this essential organelle. Conventional proteomics based on isoelectric focusing and SDS-PAGE is unsuitable for hydrophobic proteins and therefore does not allow the identification of many components of the respiratory complexes. To identify such proteins, we have used blue-native PAGE to fractionate protein complexes in their native state, followed by SDS-PAGE to separate component subunits of each complex. A total of 40 protein spots were reproducibly resolved, and 29 were identified by means of mass spectrometry, thus giving a map of the most abundant complexes in plant mitochondria. Chaperones; transporters; novel proteins; and proteins involved in the respiratory chain, the citric acid cycle, amino acid and carbon metabolism, and stress response were identified. This study gives new insight on the role and functioning of well-characterised and recently identified mitochondrial proteins by localising them to specific complexes. It also identifies novel proteins in plant mitochondria.